2018
DOI: 10.1016/j.ijid.2018.04.4322
|View full text |Cite
|
Sign up to set email alerts
|

The fifth influenza A(H7N9) epidemic: A family cluster of infection in Suzhou city of China, 2016

Abstract: Human-to-human transmission of influenza A(H7N9) virus most likely occurred in this household. The three-amino-acid mutations in HA protein were discovered in this study, which might have increased the binding affinity of influenza A(H7N9) virus to the receptor on trachea epithelial cells to facilitate viral transmission among humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…If the virus becomes enzootic among poultry in rural areas of Chongqing, it would pose a long-term threat to public health and the poultry industry. Influenza A virus mutated frequently (Wang et al, 2014), and several studies have already reported mutations of influenza A (H7N9) virus related to high pathogenicity to poultry (Quan et al, 2018;Ke et al, 2017), increasing binding affinity to facilitate viral transmission (Wang et al, 2018), reducing sensitivity to oseltamivir , and the increased virulence and expanded host range to ducks . Furthermore, influenza A (H7N9) virus might re-assort with other subtype influenza A virus (Zhu et al, 2013;Chen et al, 2016) with human and some animals acting as mixing vessels.…”
Section: Discussionmentioning
confidence: 99%
“…If the virus becomes enzootic among poultry in rural areas of Chongqing, it would pose a long-term threat to public health and the poultry industry. Influenza A virus mutated frequently (Wang et al, 2014), and several studies have already reported mutations of influenza A (H7N9) virus related to high pathogenicity to poultry (Quan et al, 2018;Ke et al, 2017), increasing binding affinity to facilitate viral transmission (Wang et al, 2018), reducing sensitivity to oseltamivir , and the increased virulence and expanded host range to ducks . Furthermore, influenza A (H7N9) virus might re-assort with other subtype influenza A virus (Zhu et al, 2013;Chen et al, 2016) with human and some animals acting as mixing vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analyses were often carried out when human infections were identified, and genetically closely related H7N9 viruses were often isolated from chickens or environmental samples, mostly from the exposed live poultry markets (Shi et al 2013a). There were also several reports of clusters of human infection cases (Ding et al 2014;Xiao et al 2014;Mao et al 2015;Yi et al 2015;Xie et al 2017;Guo et al 2018;Wang et al 2018;Zhang et al 2019), although there remains no evidence of sustained human-to-human transmission (Hu et al 2014;Dong et al 2017;Liu et al 2017;Wang et al 2019).…”
Section: Emergence and Genetic Evolutionmentioning
confidence: 99%
“…The main source of human infection with H7N9 is believed to be live poultry. Limited human-to-human transmission exists sporadically, and no evidence of multigenerational transmission currently exists [23]. In addition to the epidemiological history and clinical symptoms, the only way to diagnose H7N9 virus infection is to detect the H7N9 pathogen.…”
Section: Diagnosismentioning
confidence: 99%
“…Patients with H7N9 can also serve as a source of infection. They should be isolated and treated to avoid nosocomial infection [23,45]. The H7N9 virus has also been detected in poultry eggs, representing a potential source of infection; however, no relevant evidence of such transmission has been noted [45].…”
Section: Source Of Infectionmentioning
confidence: 99%